ANALISIS PENGELOLAAN KONTEN MEDIA SOSIAL PT TRANSPORTASI JAKARTA DALAM MEMBENTUK BRAND AWARENESS (Studi Kasus pada Instagram @pt_transjakarta) - Adriany, Novira Wieke (MediaKom : Jurnal Ilmiah Komunikasi, 2023)
The rapid development of technology has brought many benefits to many aspects of life, one of them is the rise of the Internet or digitalization. This study examines Social Media Content Management Analysis of PT Transportasi Jakarta in Forming Brand Awareness. The purpose of this study is to see the effectiveness of the management of social media content of PT Transportation Jakarta, in particular instagram carried out by PT Transportasi Jakarta against brand awareness of PT Transportasi Jakarta. This research uses a qualitative approach with case study methods. The data collection technique was conducted using interviews as well as supporting documents related to content management on the instagram media @pt_transjakarta. The results of this study show that the wider public has been aware of the services of PT Transportation Jakarta and the content produced today has the diversity to reach more people. However, the public expects Transjakarta to provide more frequently content in the form of information about its route services or operations. Keywords: social media content management, social media, brand awareness